Against all odds - Alymbekova, Cholpon Samakovna (KDI School, 2012)
This paper attempts to demonstrate that democratic transformation in Kyrgyzstan is the natural outgrowth of a number of factors that make Kyrgyzstan a special case in Central Asia and a participant in the Fourth Wave of democracy. The prospect of a stable democratic Kyrgyzstan is promising, as essential elements of democracy are present within the culture but the role of external forces might not always be encouraging its further development. While discussing what makes democracy fragile, this paper will reveal that a successful transformation has been achieved thanks to the strength of internal factors committed to the removal of the authoritarian regime and despite a number of external factors that have created obstacles for democracy, making the struggle even more difficult.
Thesis(Master) --KDI School:Master of Public Policy,2012